The Future Geographies of Food: Possibilities, Contradictions, and Opportunities. - Kansanga, Moses; WinklerPrins, Antoinette M. (Geographical Review)
Amid deepening socioecological concerns, the future geography of food promises to become more contested in the next few decades. This special issue, which is an offshoot of the American Geographical Society's symposium on the Future of Food, brings together a rich blend of articles that interrogate diverse aspects of the future of food, including questions on the promise of high-tech modes of food production, alternative food sources for the future, and smallholder agriculture. In this introduction, we synthesize these debates across articles and highlight what is at stake for the future of food. While we may not be able to accurately predict what we will eat in the years ahead, food will change tremendously and foodways will be shaped by ongoing ontological politics and contestations over what constitutes "clean" and "healthy" food, and how to produce it. Globalization will shape place-based food practices, yet food will retain its cultural meaning even as traditional foodways are shaped by culinary practices and products from distant geographies. Similarly, small agriculture promises to be resilient and will continue to foreground food security for many across the world, particularly in the Global South.